VOCALIZATION OF ASIAN STRIPED TREE FROGS, Polypedates leucomystax (GRAVENHORST, 1829) AND P. iskandari RIYANTO, MUMPUNI & McGUIRE, 2011 - Hellen Kurniati (BRIN Publishing (Penerbit BRIN), 2011)
Morphometric study has showed that Asian Striped Tree Frog popula-tions from Sulawesi can be separated from populations discovered in other islands (Sumatra, Java and Kalimantan) and become accepted as a new species, namely Polypedates iskandari (Riyanto et.al., 2011). However, the results on analysis of vocalizations sequences have indicated that, P. iskandari and P. leucomystax from Java population use similar acoustic bandwidth frequencies in the major call. The different between the two species can only be found in minor calls; P. iskandari has a higher dominant frequency range than P. leucomystax. This study shows that minor calls are not important in communication among males. Therefore, based on acoustic analysis, there is no sufficient evidence to classify the Sulawesi population of P. leucomystax as a new species.